2017
DOI: 10.13189/ujp.2017.050302
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Trait Mindfulness and False Memory: A Bilingual Deese-Roediger-McDermott Paradigm

Abstract: Mindfulness-based interventions are known to increase false memory. However, high trait mindfulness is associated with an external encoding style and field independence, which in turn are associated with low false memory. The present study used a bilingual context to disentangle these contrasting findings. Sixty ChineseEnglish bilinguals completed a Deese-Roediger-McDermott (DRM) false recognition task and were evaluated using the Mindfulness Attention Awareness Scale (MAAS). Results showed negative and positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
1
10
1
Order By: Relevance
“…However, more recent conceptualizations consider mindfulness as a multidimensional construct (Baer et al, 2006). In the context of studied items possessing higher distinctiveness, we expect to observe a positive correlation between dispositional mindfulness and memory sensitivity, but a negative correlation with response bias, as suggested by Yeh and Lu (2017) observations.…”
Section: Current Investigationmentioning
confidence: 63%
See 1 more Smart Citation
“…However, more recent conceptualizations consider mindfulness as a multidimensional construct (Baer et al, 2006). In the context of studied items possessing higher distinctiveness, we expect to observe a positive correlation between dispositional mindfulness and memory sensitivity, but a negative correlation with response bias, as suggested by Yeh and Lu (2017) observations.…”
Section: Current Investigationmentioning
confidence: 63%
“…To our knowledge, only one study investigated the impact of dispositional mindfulness on false memory in the DRM context (Yeh & Lu, 2017 ). In this study, a set of Chinese and English words were used in the encoding and the retrieval phase, either in congruent (e.g., English at encoding and retrieval) or incongruent (e.g., Chinese at encoding and English at retrieval) conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In the cross-language condition, only a marginal difference was observed between the false recognition of positive and negative CLs, suggesting a trend of valence effect caused by the mix of two languages; moreover, similar to the results in English condition, the false recognition of CLs was not associated with trait mindfulness. Furthermore, we compared the results in the present study with those of another previous study (Yeh & Lu, 2017); a similarity was observed in that both assessed the relationship between trait mindfulness and DRM false memory for Chinese-English bilinguals. However, the negative correlation of trait mindfulness with false memory under within-language conditions and positive correlation with false memory in cross-language conditions were results that were not replicated in the present study.…”
Section: Discussionmentioning
confidence: 68%
“…One possible reason for this discrepancy is the difference between these two studies regarding source-monitoring requirements at retrieval. In a study conducted by Yeh and Lu (2017), participants were asked to form "old" decisions based on language-specific measurements (i.e., being instructed to only respond "yes" if a word appeared in the same language); therefore, the verbatim trace was essential for establishing a distinction between old and new words. In this study, however, language-specific recognition was encouraged in participants, but if they could not retrieve the vivid verbatim trace then they were permitted to select one option from the two "old" decisions (i.e., respond "1" if a test word was presented in the same language in the study or "2" if a test word was presented in a different language in the study).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation